2022
DOI: 10.3389/fcimb.2022.858196
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiology of Acute Exacerbations in Chronic Rhinosinusitis - A Systematic Review

Abstract: BackgroundAcute exacerbations (AE) in chronic rhinosinusitis (CRS) are a common and important clinical issue. However, relatively little is known regarding the underlying microbiology that drives exacerbations or how it relates to the microbiome of CRS. The purpose of this study is to examine the literature to characterize the microbiome associated with acute exacerbations in a chronic rhinosinusitis setting. Understanding this disease process may facilitate targeted antibiotic therapy, reduced antibiotic resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Various studies have linked S. aureus to the CRS pathophysiology, in particular the more severe disease phenotypes [ 6 , 7 ]. S. aureus is the most frequently cultured bacteria in patients with CRS exacerbation [ 8 ] and influences inflammation by disrupting epithelial barrier function, impairing mucociliary clearance and inducing innate and adaptive immune responses, which may result in polyp formation [ 6 ]. Clinically, rhinosinusitis can be classified according to the duration of symptoms, including acute, subacute, or chronic [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have linked S. aureus to the CRS pathophysiology, in particular the more severe disease phenotypes [ 6 , 7 ]. S. aureus is the most frequently cultured bacteria in patients with CRS exacerbation [ 8 ] and influences inflammation by disrupting epithelial barrier function, impairing mucociliary clearance and inducing innate and adaptive immune responses, which may result in polyp formation [ 6 ]. Clinically, rhinosinusitis can be classified according to the duration of symptoms, including acute, subacute, or chronic [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have identified Staphylococcus aureus as a potential driver of disease in CRS [ 8 ]. Indeed, S. aureus is often cultured from the sinuses of CRS patients during the exacerbation of the disease [ 9 ]. Furthermore, S. aureus induces the secretion of various cytokines such as thymic stromal lymphopoietin (TSLP), IL-33 and IL-22 in nasal mucosa [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have associated Staphylococcus aureus as a potential driver of disease in CRS (Vickery, Ramakrishnan, & Suh, 2019). Indeed, S. aureus is often cultured from the sinuses of CRS patients during the exacerbation of the disease (Okifo, Ray, & Gudis, 2022). Furthermore, S. aureus induces secretion of various cytokines such as thymic stromal lymphopoietin (TSLP), IL-33 and IL-22 in nasal mucosa (Lan et al, 2018;Mulcahy, Leech, Renauld, Mills, & McLoughlin, 2016).…”
Section: Introductionmentioning
confidence: 99%